CORRELATION STUDY OF QUALITY OF LIFE OF PREGNANT WOMEN AND MATERNAL FETAL ATTACHMENT - Devi Permatasari; Sri Sat Titi Hamranani; Andriyani (Jurnal SMART Keperawatan, 2025)
Background: Pregnancy is a natural process involving the conception of an ovum and sperm, leading to physical and psychological changes that increase the risk of mental and physical health issues. Pregnant women's quality of life is influenced by their biological, physical, mental, and social functions. Conditions like hyperemesis, discomfort, anxiety, and lack of support networks can impact their quality of life. Maternal Fetal Attachment (MFA) plays a crucial role in maternal and fetal health, with high MFA scores indicating better self-care and pregnancy behavior. Objective: This research about points to decide the relationship between the quality of life of pregnant women and maternal fetal attachment. Methods: Quantitative correlational study with a sample of 30 pregnant women. Accidental sampling technique using Prenatal Attachment Inventory Questionnaire and Quality of Life (QoL). Data analysis using Kendall Tau. Results: The age range of respondents was 20-35 years, the majority were high school graduates (63.3%), multigravida (76.75). The quality of life of pregnant women was good (80%). Maternal Fetal Attachment was high (25 respondents (83.3%). The results of Kendal Tau showed a p value of 0.017 or p-value <α 0.05. Conclusion: There's relationship between quality of life of pregnancy and maternal-fetal connection in pregnant mother. Mothers are recommended to increase maternal-fetal attachment Strengthening and pay attention to mental health and emotional support.